Influence of the principal's leadership styles in the evaluation of the quality of the management in the educational institution 3071 “Manuel T. García Cerrón” Ugel 04, of the Puente Piedra 2016 district - Trujillo Quezada, María Soledad (2019)
This research aims to determine the relationship between the leadership styles of the director and the assessment of the quality of management in the educational institution 3071 "Manuel T. Garcia Cerrón" Ugel 04 Puente Piedra district. 2016. It is an investigation that corresponds to the type of basic study, their level is descriptive and correlational design. For data collection questionnaires Leadership Styles and questionnaire quality of management quality were used, they were validated by expert judgment (three judges) and then subjected to the test of Cronbach's alpha and style leadership yielded a value of 0.907 and the quality of management was 0.763. The data were subjected to Kosmorov Smirnov test, as resulting resorted to the Spearman correlation test. The sample consisted of 121 parents, 70 teachers and 134 students, who were chosen intentionally nonprobability. The data were processed using the statistical software SPSS version 21, the results indicated that there is evidence of significant correlation with a good level (Rho Spearman is, 784) between the styles of leadership and quality assessment of educational management, in addition to p value less than 0.05 is found. The analysis indicates that the lowest correlation is in the dimensions of authoritarian leadership and quality management with a value of Rho Spearman, 377) and charismatic leadership with the quality of management (Spearman rho, 397).